KOMUNIKASI INTERPERSONAL ANTARA PELATIH DAN ATLET DISABILITAS DALAM MENUMBUHKAN MOTIVASI DAN PRESTASI ( STUDI DESKRIPTIF ATLET TENIS MEJA DISABILITAS NPCI DKI JAKARTA) - Hani Tri Azhari; Yeni Nuraeni; Rina Astriani (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Interpersonal communication is needed between coaches and athletes with disabilities in order to create an approach that is expected to foster motivation to practice. In addition, the training also provides non-technical guidance to train athletes with mental disabilities so that athletes have a sense of self-confidence and achievement. The purpose of this study was to determine interpersonal communication between coaches and table tennis athletes with disabilities and their implementation in growing self-confidence and achievement between coaches and table tennis with disabilities NPCI DKI Jakarta. The method used in this study uses a qualitative approach by conducting a descriptive study on the object. The paradigm used in this research is using constructivism paradigm. Data processing techniques through interviews and observations. Based on the discussion, the relationship that exists between coaches and athletes with disabilities has a stage to foster trust between coaches and table athletes with disabilities at NPCI DKI Jakarta. Trust that grows between individuals gives birth to a motivation that results in achievements for NPCI DKI Jakarta athletes.